Reproductive Immunology in Mares - Risvanli, Ali (Academic Journals Inc, 2011)
In mare breeding, infertility arising from various causes, leads to important economical losses. In these animals, infertility can occur due to several factors such as infections, genetics, hormones and management problems and other etiologies that cannot be clearly demonstrated. With regard to this aspect, idiopathic infertility remains an important subject in mare breeding. Recently, immunological infertility - both humoral and cellular - has been frequently discussed. The causes of the infertility arising from humoral immunity, which is considered within the context of antigen-antibody reactions, include anti-sperm antibodies (ASA), anti-zona pellucida antibodies (anti-ZP antibodies) and anti-ovarian stroma antibodies. These antibodies affect the fertility in a broad spectrum, ranging from subfertility to sterility. Cellular immunity play an important role, especially in the occurrence of bacterial endometritis. On the other hand, there are many researches emphasizing the use of leukocytes in the treatment of endometritis in mares.
Keywords: Reproductive; immunology; mare